Analisis Efektifitas dan Produktifitas Kerja Front Desk Agent dalam Meningkatkan Pelayanan Hotel di Jember - Hadi Jatmiko; Syah Riza Octavy Sandy (STIEPAR YAPARI Bandung, 2023)
This study aims to analyze the influence of the effectiveness and productivity of Front Desk Agents in improving hotel services in Jember. While the sampling technique used is: Quota Sampling Method, which is a way of taking samples that have been determined/rationed beforehand. Samples for hotel guests were taken in several hotels in the city of Jember as many as 80 respondents. Structured interviews with Managers and hotel management associations. The data analysis technique used in this study is descriptive qualitative, namely data analysis using detailed explanations obtained from hotel managers, employees, guests who are staying overnight which are descriptive in nature. The results of the regression test show that the variables of work effectiveness and work productivity are proven to have a joint effect on the quality of Front Desk Agent services at hotels in Jember City. This illustrates that in order to improve the quality of Front Desk Agent services at hotels in Jember City, the hotel must consider the factors of work effectiveness and work productivity. The results of identifying the factors that influence the quality of Front Desk Agent services at hotels in Jember, Simultaneously: Work effectiveness and work productivity are proven to have a joint effect on the quality of Front Desk Agent services at hotels in Jember City. The results of the analysis of the coefficient of determination show that 41,7% of the variation in the change in the quality of Front Desk Agent services at hotels in Jember is explained by the factors of work effectiveness and work productivity.